(untitled) - Patterson, Thomas E. (Boston, 2005)
In the two years that have passed since the second edition of THE AMERICAN DEMOCRACY, our nation has witnessed a tremendous amount of conflict both at home and abroad. This Election Edition contains coverage of the 1996 campaigns, conventions, and elections. Today's college students are not only reading history - they're watching it happen, and certainly no academic discipline is changing faster than political science. THE AMERICAN DEMOCRACY is a text that helps students keep pace with those changes by challenging them to think about how today's issues affect the institutions and processes of government in the United States. The text has been thoroughly updated to include the latest scholarship and the most recent political developments, including the 1994 elections, the Republican-controlled Congress, the new federalism, welfare reform measures, the immigration controversy, the National Performance Review and other effects to "downsize" governmental administration, regulatory policy reform, GATT, and the changes in Haiti, Bosnia, Somalia, the UN, the Republican Contract with America, the Oklahoma City bombing, and NATO.